IMPLEMENTASI METODE TALKING STICK DALAM MENINGKATKAN MINAT BELAJAR SISWA KELAS VII PADA MATA PELAJARAN PAI DI SMP MERDEKA SUMBERSARI SRONO - Ahmad Izza Muttaqin; Anis Fauzi; Vina Rohmatul Ummah; Imelda Adibatul Aziz (INCARE, International Journal of Educational Resources, 2021)
This study describes the application of the Talking Stick method in increasing student interest in learning PAI VII grade at Merdeka Middle School. Because the process of applying conventional methods that result in low student interest in learning. Therefore the PAI teacher in Merdeka Middle School applies the Talking Stick method which aims to create a pleasant learning atmosphere and students become more active so that it can increase student interest in learning. This type of research uses qualitative descriptive research. The object of this research is the Implementation of the Talking Stick Method and PAI subjects while the research subjects are Grade VII students and PAI subject teachers. In the process of collecting data using several methods, namely the method of observation, interviews, and documentation. Data analysis techniques used are data condensation, data presentation, and drawing conclusions. In this study there are several data validity, namely Triangulation as data collection techniques, source triangulation, time triangulation. The results of this study are the implementation of the Talking Stick method by the PAI teacher running effectively. Many students tend to be more active, the class atmosphere becomes more lively and students feel happy. Thus it can be concluded that the implementation of the Talking Stick method students 'interest in learning activities can attract students' attention and will greatly affect student interest in learning.